SYSTEMATIC LITERATURE REVIEW (SLR): FENOMENA IMPULSIVE BUYING DALAM LAYANAN BUY NOW PAY LATER (BNPL) SHOPEE DARI PERSPEKTIF EKONOMI SYARIAH - Selvina Adhani, Adinda; Nurhayati; Mugiyati (JURNAL ILMIAH EDUNOMIKA, 2025)
The rapid expansion of e-commerce and digital financial services has transformed consumer behavior, particularly among Generation Z. One notable innovation is the Buy Now Pay Later (BNPL) system, known on the Shopee platform as Shopee PayLater. While this feature offers flexibility and instant access to goods, it also increases impulsive buying behavior and overconsumption, raising concerns from the perspective of Islamic economics. This study aims to analyze the phenomenon of impulsive buying through Shopee PayLater using the Systematic Literature Review (SLR) method. Fifteen academic articles published within the last five years were reviewed to explore the relationship between BNPL services, consumer behavior, and Islamic economic values. The findings reveal that BNPL significantly contributes to impulsive purchases and potential financial instability among young consumers. From the perspective of Maqashid Syariah, such behavior is associated with israf (extravagance) and gharar (uncertainty), which contradict the principle of protecting wealth (hifz al-mal). The study concludes that strengthening Islamic financial literacy is essential to prevent excessive consumption in the digital economy and to ensure that financial practices remain aligned with ethical and sustainable Islamic principles.